IMPACT OF THE SPECIFIC FEATURES OF DISEASE COURSE AND THERAPY ON QUALITY OF LIFE IN PATIENTS WITH ANKYLOSING SPONDYLITIS - N. A. Kuznetsova; G. B. Kolotova (Научно-практическая ревматология, 2015)
Objective: to investigate the impact of specific features of the course of ankylosing spondylitis (AS), sociodemographic factors, and therapy on quality of life (QL) in patients with this disease. Subjects and methods. The results of studying QL (with the SF-36 questionnaire) in 90 adult patients with AS versus 45 healthy individuals (a control group) were presented. Within 6 months before study inclusion, 30 patients with AS received only nonsteroidal anti-inflammatory drugs (NSAIDs); 27 – NSAIDs + sulfasalazine (SULF), 15 – NSAIDs + infliximab (INF); 18 (20%) patients were not systematically treated and were excluded from the study. A control group comprised 45 apparently healthy volunteers (32 men and 13 women); both groups were matched for gender and age. Results and discussion. The patients with AS were found to have lower physical and psychological QL scores than the controls (p < 0.001). In those with AS, QL worsened as the inflammatory disease activity, functional limitations, articular manifestations and enthesitis increased. Coxitis detected in 76.7% of the patients had a negative effect on rolephysical functioning. The sociodemographic factors were not found to have a statistically significant influence on QL in the patients with AS. The QL scores were higher in the patients taking INF in combination with NSAIDs. Evaluation of the impact of performed drug therapy on QL in the patients receiving SULF versus the controls revealed statistically significant worse scores in all the scales of the SF-36 questionnaire (p < 0.001). In the patients who had NSAIDs only, the QL scores were also worse than those in the control group (p < 0.001). According to the data of the SF-36 questionnaire, a number of QL scores in the patients receiving INF + NSAIDs proved to be similar in the apparently healthy individuals. Thus, the patients with AS have considerably lower physical and psychological QL scores than the healthy people. QL worsens as the inflammatory activity of AS and functional limitations increase. No influence of sociodemographic factors on QL was found in the patients with AS. Therapy with INF in combination with NSAIDs ensured higher QL in these patients than did other treatments.